Electric Circuit Analysis. - Kumar, K.S.Suresh. (2013)
Electric Circuit Analysis is designed to serve as a textbook for undergraduate course on basic electric circuits. The book builds on the subject from its basic principles. Spread over fourteen chapters, the book can be taught with varying degree of emphasis based on the course requirement. Written in a student-friendly manner, its narrative style places adequate stress on the principles that govern the behaviour of electric circuits.
10.4.2 The Time Constant 's ' of a Series RL Circuit.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2018. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books